Constipation symptoms are associated with worse cognitive outcomes in older adults without dementia - Liu, Xiaochang; Zhou, Juan; Xie, Xinyan; Zheng, Wenzhe; Liu, Dan; Cheng, Guirong; Hu, Feifei; Wang, Junyi; Cai, Cheng; Liu, Jing; Nie, Qianqian; Li, Shiyue; et al. (Frontiers in Nutrition, 2025)
BackgroundConstipation is correlated with cognitive impairment; however, the association of constipation symptoms with cognitive domains remains unclear. This study aimed to investigate this association.MethodsParticipants aged 65 and older underwent neuropsychological, clinical, and laboratory examinations. Clinicians diagnosed constipation using the Rome IV criteria. Multivariate logistic regression assessed the odds ratios (ORs) and 95% confidence intervals (CIs) for mild cognitive impairment (MCI) and multi-domain cognitive impairments in relation to constipation and its specific symptoms. Mediation analysis was conducted to examine the effects of depressive symptoms.ResultsConstipation was diagnosed in 9,417 participants without dementia [mean (standard deviation) age: 72.0 (5.6) years], while constipation symptoms were recorded in 3,344 individuals [mean (standard deviation) age: 72.6 (5.5) years]. Of the overall population, 1,895 (20.1%) were diagnosed with constipation. Constipation was associated with a higher MCI risk (OR: 1.177, 95% CI: 1.047–1.323), worse performance on language (OR: 1.133, 95% CI: 1.011–1.270), and executive function (OR: 1.386, 95% CI: 1.130–1.701). A higher MCI risk was associated with constipation symptoms: bowel movements every 3 or more days (OR: 1.391, 95% CI: 1.011–1.914), defecation difficulty (OR: 1.278, 95% CI: 1.002–1.629), and dry stools (OR: 1.326, 95% CI: 1.027–1.711). Prolonged bowel movements increased the risk of both memory and language impairment, but not MCI. Defecation difficulty was associated with memory impairment (OR: 1.309, 95% CI: 1.003–1.709), dry stools with language impairment (OR: 1.396, 95% CI: 1.088–1.791), and bowel movements every other day with executive impairment (OR: 1.761, 95% CI: 1.151–2.693). Depression mediated the association of constipation with global cognitive and language function.ConclusionIn the non-demented stage, constipation and its symptoms were associated with MCI and multi-domain cognitive impairments. These associations, along with depressive symptoms, should be further evaluated in large-scale population screenings to benefit cognitive impairment management.